Aqasid Al-Syari'ah Perspective In Polygamies: A Comparative Study Of Polygaming Rulesin Indonesia And Malaysia - Bahrum, Bahrum; M. Husein Ritonga; Bahrul Ulum (Cita konsultindo, 2023)
With a multimethodological approach, the discovery, reasoning and integration of Islamic law regarding polygamy in positive law in Indonesia and positive law in Malaysia is very urgent to be reviewed. Because Islamic law, which is shalih li kulli al-hal wa al-makan, must actually be integrated with positive law in Indonesia and Malaysia . Determination of legal understanding of the maqāsyid syarī'ah review of polygamy regulations in Indonesia and Malaysia must go through an interpretation process in the form of an in-depth understanding of Law Number 1 of 1974 and other regulations that apply in both countries. Thus, the public can find out the reasons ('illaṯ) and objectives that underlie the enactment of the law with the principles of ushul al-fiqh as the basis for making or determining the law. The many phenomena of polygamy in this Muslim-majority country should be a common concern. So it is not excessive when questioned about the extent to which the spirit of shari'ah has a significant effect on the life of the nation and state .